Pengaruh Stock Ownership Terhadap Income Smoothing Dengan Company Size Sebagai Pemoderasi - Christiana Meilani; Muhammad Nuryatno (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The study aims to determine the effect of Institutional Ownership, Managerial Ownership, dan Public Ownership on Income Smoothing with Company Size as Moderating in consumer non-cyclical sector companies listed on the Indonesia Stock Exchange (BEI) Period 2020-2022. The research was conducted using a quantitative methods. The data used in this study were secondary data obtained from the financial statements of consumer non-cyclical sector companies listed on the Indonesia Stock Exchange (BEI) Period 2020-2022. The sampling technique used was by purposive sampling with predetermined criteria resulting in 40 companies for 3 years and then the total sample of 120 data. The research analysis method is with logistic regression and uses IBM SPSS to test and process this research data. The results of the research concluded that institutional ownership, managerial ownership, and public ownership had a positive effect on income smoothing. Company size as a moderator is able to strengthen the positive influence of institutional ownership on income smoothing. However, company size is not able to strengthen the positive influence of managerial ownership, and public ownership on income smoothing. Keywords: Company Size; Income Smoothing; Institutional Ownership; Managerial Ownership; Public Ownership.